CITRA PEREMPUAN BETAWI DALAM NASKAH PERIYASAN BAGUS KARYA USMAN BIN YAHYA - Dania, Dania; Kosasih, Ade; Ikhwan, Ikhwan; Ma’mun, Titin Nurhayati (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2024)
This research raises the issue of women in the manuscript by Usman bin Yahya entitled Periyasan Bagus. This research to depict Betawi women in the 19th century. To reveal the contents of the manuscript text, the first step is to read the manuscript and translate. Then proceed with analyzing the structure of the content using a mimetic approach which produces isotopy and a psychological approach regarding women's self-image using Satoto' theory (1994). The results obtained show that the Periyasan Bagus manuscript depicts women in psychological aspects and social aspects. The psychological image of Betawi women depicted in the PB text is Betawi women who say dzikir and Betawi women who always guard or observe prayers. Meanwhile, the image of women in the social aspect is that of Betawi women who behave well, guard their words and sweeten their views both towards their parents and husband.